The influence of the electrode dimension on the detection sensitivity of electric cell–substrate impedance sensing (ECIS) and its mathematical modeling - Zhang, Xudong; Wang, William; Nordin, Anis Nurashikin; Li, Fang; Jang, Sunghoon; Voiculescu, Ioana R. (Elsevier B.V., 2017)
Detection sensitivity is a crucial criterion in the design and application of ECIS sensors. The influence of sensing electrode dimension on detection sensitivity is investigated in this paper. Eight types of ECIS sensors were fabricated, and their experimental results reveal that smaller-radius working electrodes generate more sensitive impedance shift to cell density change. Also, the smaller radius of working electrodes yield higher impedance values, which improves signal-to-noise ratio. In a range from 1.0 mm to 3.5 mm, the distance between the working and counter electrodes does not affect impedance measurements. However, the distance should be large enough to prevent the current from directly bypassing the cells between the electrodes. A mathematical model has been developed to analyze the distribution of electric potential and current over the sensing electrodes of ECIS sensors, which is helpful in understanding the mechanisms of ECIS. This mathematical model, supported by experimental data and finite element analysis, is able to illustrate a quantitative relationship between cell impedance and cell characteristics. This model can be used to optimize the design of ECIS sensors and interpret cell behavior.